Training and competency challenges of municipal councillors in the Mangaung metropolitan municipality in the Free State province - Taaibosch, Thoriso April ([Bloemfontein] : Central University of Technology, Free State, 2015)
The study examines training and competency challenges of municipal councillors in the Mangaung Metropolitan Municipality in the Free State province. The main objective of this study is to determine the training needs and competency challenges of municipal and ward councillors in the Mangaung Metropolitan Municipality and what training should be recommended to address these challenges. The value of municipal councillors in respect of service delivery is being increasingly questioned in the wake of recent service delivery protests, and various negative reporting on the state of the local sphere of government. The current state of affairs for municipal councillors raises lots of questions about the required skills to successfully execute their mandate. To address these challenges, four objectives were set to guide the study. As a result the study investigates through the legislative framework, roles, functions and responsibilities of ward and municipal councillors, and their contributions towards effective and efficient municipal government. For the realisation of the aim and objectives of this study, qualitative research methodology is adopted. An interview programme was utilised as a tool that contains the predetermined questions prepared in order to acquire insight, knowledge and application of the people who are involved and familiar with the ward and municipal councillor processes and challenges. The literature study is based on the requirements of a qualitative study, which includes extensive literature, legislation, policy documents, journal articles, books, conference papers, internet and government reports about, the purpose of local government, the developmental role of local government as well as the requirements, purpose, roles, functions and mandate of municipal councillors and ward councillors. An empirical study, by a process of structured interviews with selected councilors (municipal representative and ward councilors) was also be administered.
Thesis (Masters Technologiae: Public Management) -- Central University of Technology, Free State, 2015
Keywords: Central University of Technology, Free State -- Dissertations; Municipal officials and employees -- Training of -- South Africa -- Mangaung; Metropolitan government -- South Africa -- Mangaung; Local government -- South Africa -- Mangaung; Dissertations, academic -- South Africa -- Bloemfontein